Understanding the CD28/CTLA‐4 (CD152) Pathway and Its Implications for Costimulatory Blockade. Issue 9 (6th August 2014) - Gardner, D.; Jeffery, L. E.; Sansom, D. M.
<x xml:space="preserve">Abstract</x> T cell activation is a key event in the adaptive immune system and vital in the generation of protective cellular and humoral immunity. Activation is required to generate CD4 effector T cell responses and provide help for B cell and cytotoxic T cell responses. While defective T responses to foreign antigen result in infectious pathology, over‐reactive T cell responses against self‐antigens result in autoimmunity and, in a transplantation setting, tissue rejection. Understanding how T cell activation is normally regulated is critical to therapeutic intervention and the CD28/CTLA‐4 (CD152) pathway represents the initial activation checkpoint in molecular terms. In particular, while the CTLA‐4 pathway is well established as an essential regulator of self‐reactivity, its mechanism of action is still uncertain. Such mechanistic issues are important given its central position in T cell activation and the increasing number of therapeutic modalities aimed at manipulating the CD28/CTLA‐4 pathway. Here, we provide an updated view of CTLA‐4 biology, reviewing the established features of the system and highlighting its interplay with CD28. We then discuss how recent progress in our understanding of this pathway affects our interpretations following intervention.